Post a New Question

precal

posted by .

Solve for y:
(y-(10/y))^2+6(y-(10/y))-27=0

  • precal -

    (y-(10/y))^2+6(y-(10/y))-27=0
    his is just like the other one: Let u=y-1/y and you have

    u^2 + 6u -27 = 0
    (u+9)(u-3) = 0
    (y - 10/y + 9)(y - 10/y - 3) = 0
    (y^2 + 9y - 10)(y^2 - 3y - 10) = 0
    (y+10)(y-1)(y-5)(y+3) = 0

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. precal

    solve by subsituting 5x+4y=7 x-3y=9
  2. precal

    solve for x: (x^2-2x)^2 -11(x^2-2x)+24
  3. PreCal

    Solve for x. -3x^2+8=-4
  4. PreCal

    Solve The Inequality 0 < -9x/x-x^2
  5. Precal

    Solve for x 9^(x^2) = 3^(-5x-2)
  6. Precal

    Solve for x 9^x - 4 * 3^x +3=0 I know the 9^x = (3^x)^2
  7. precal

    solve for x: 4sin^2x= 4cosx+1
  8. precal

    solve for x: 4sin^2x= 4cosx+1
  9. Math/Precal

    How do i solve for x: (9^2x)/(27^x-2)=81^3x-4
  10. Precal

    solve for x if -2=log(3x+5)

More Similar Questions

Post a New Question